Identify factors related to the unmet need for family planning in women of childbearing age - Poul, Andrew; Seri Ani, Luh; Lubis, Dinar Saurmari (Institute of Computer Science (IOCS), 2024)
Unmet family planning needs in women of childbearing age (WCA) are known to increase fertility and mortality rates in mothers and children. Prepositioning, enabling, and reinforcing factors related to unmet needs have been widely studied, but have not found consistent results. This study aims to determine the relationship between predisposing, enabling, and reinforcing factors with the incidence of unmet needs in WCA. The cross-sectional study was conducted at WCA in West Denpasar District. A total of 120 participating WCA were selected using the multistage method. Data was collected by structured interviews. Women of childbearing age who met the inclusion and exclusion criteria were interviewed at their respective homes. Univariate analyses were performed to obtain the proportion of unmet need incidence in women of childbearing age. Logistic regression tests are performed to determine factors related to unmet need events. The results of the study found the incidence of unmet need FP in WCA at 59.2%. Unmet need events in WCA are associated with predisposing factors consisting of age, ability in decision making, enabling factors, namely the distance of family planning service places to home and reinforcing factors, namely officer support and history of family planning use. This study suggests increasing access to family planning services and dissemination of information about the use of family planning in WCA to reduce the incidence of unmet need FP in WCA.